Compression characteristic of unsaturated residual soils by constant rate of strain test - Tan, Wei Jian. (2011)
In geotechnical engineering, residual soils have been of great concern in recent years. This is mainly due to more developments being built on residual soils. One important characteristic of residual soils is its unsaturated nature and the existence of negative pore-water pressure. This project aims to provide a better understanding of the settlement behavior of unsaturated residual soils.